Governmentality, necropolitics, black childhood and education of the face - José Da Silva, Divino [UNESP]; de Almeida, Jonas Rangel [UNESP]; Pagni, Pedro Angelo [UNESP] (Universidade de Estado do Rio de Janeiro, 2021)
In this article, we seek to discuss the recurrence of racism and prejudice toward black lives and childhoods, in spite of repeated initiatives to overcome it by social and educational policy-makers. Following the investigations launched by Michel Foucault on the biopower hypothesis, we revisit some of his interpreters, with the objective of discussing the challenges posed by racism to pedagogical provisions for black children and—following on a concept offered by Emmanuel Levinas-an education of the Face (el Rostro), as a weapon in the political field of struggle against the thanatological dimension of biopolitics. To do so, we retrace some scenes from the history of inclusion devices – especially those policies aimed at black populations. We reflect on the racism embedded in our historical unconscious and discuss how it affects the education of the black Face in our country. We problematize the peculiarities of Brazilian racial prejudice and explore its necropolitical positioning when it comes to the governance of black childhoods. We conclude that the current form of governmentality and education needs a movement of de-rostification—deconstuction of the black Face-in order to identify a future for black children that makes it possible to rise up against the hegemonic order of the white-male-heterosexual-christian-European, and to create processes of subjectivation that can build solidarity with the multiplicity of others-becoming-minoritarian.
Necropolítica, gobierno sobre las infancias y educación del rostro
Necropolítica, governo sobre as infâncias negras e educação do rosto
Keywords: Becoming-minority; Black childhoods; Education of the face; Governmentality; Necropolitics